THE IMPACT OF EXPERIENTIAL MARKETING ON WORD OF MOUTH WITH CUSTOMER SATISFACTION AS A INTERVENING VARIABLE - Muhammad, Muhammad; Artanti, Yessy (Jurnal Dinamika Manajemen, 2016)
PT Maktour got a predicate from the Ministry of Religous Affairs as the best special hajj and umrah Â organizer and was ranked as the Top Brand Index category travel agency in 2014. This study was to examine the impact of Experiential marketing on word of mouth (WOM) with customer satisfaction as intervening variable. The research design used hypothesis testing with a purposive sampling techniques. The respondents in this study were 105 respondents. The data were analyzed using AMOS software 20. The result showed Experiential marketing has a significant on customer satisfaction and WOM.